PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE, LIKUIDITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Joel Pardin Malau, 14.05.52.0182; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2019)
The purpose of this study is to examine the effect of Good Corporate Governance, Liquidity and Corporate Growth on the performance of companies that participate in the 2014-2017 Corporate Governance Perception Index Program. The population is all companies that participate in the 2014-2017 Corporate Governance Perception Index Program. The sampling technique uses purposive sampling. The analytical tool used is multiple linear regression. The results of the analysis can be concluded that: Good corporate governance does not have a significant effect on company performance (ROA). Liquidity has a positive and significant effect on company performance (ROA). The company's growth has no significant effect on company performance (ROA).